Efeito da incorporação do nitrato de cério na resistência à flexão, rugosidade superficial e porosidade de uma resina acrílica termopolimerizável - Farias, Ohana Rodrigues (2017)
Introduction: The incorporation of antimicrobial agents to the acrylic resin is an alternative strategy to prevent or treat fungal infections, however, it is important that these materials do not modify the physical characteristics of the final product. Purpose: To evaluate the incorporation of the cerium nitrate on the flexural strength and surface roughness of the acrylic resin thermally activated by microwave energy (Vipi Wave). Materials and Methods: Cerium nitrate solutions were obtained in two types of solvents (10% DMSO and 5% DMSO + 5% Tween 80) in two concentrates (16xCIM: 26 mg/ml and 32xCIM: 52mg/ml), which were incorporated, creating five groups: Control Group (pure PPMA), DMSO + Cerium 16xCIM (DC 16xCIM) and 32xCIM (DC 32xCIM) and DMSO + Tween + Cerium 16xCIM (DTC 16xCIM) and 32Xcim (DTC 32Xcim). The solutions were incorporated into the thermo-polymerizable acrylic resin to develop the test specimens, elaborated according to ISO 20795-1 / 2013. The specimens were submitted to the flexural strength test at three points (n = 17), roughness analysis (Sa and Sz) by using optical profilometry (n = 19) and percentage of porosity (n=18) in x-ray computed microtomography (micro CT). The statistic analysis was performed in the IBM SPSS software (21.0). The results of flexural strength and surface roughness were analyzed by ANOVA and in complement, the Tukey test adopting a significance level of 1% (α=0.01). The porosity results was analyzed by Kruskal-Wallis e Mann Whitney U adopting a significance level of 1% (α=0.01). Results: In the flexural tests it was found that the experimental groups demonstrated a less resistance than control group (80,66 MPa; DP 11,30) (p<0.0001), with no statistics difference among themselves. In the statistical analysis of the surface roughness it was observed that all groups showed an increase in roughness in relation to the control (Sa 0,057µm; Sz 0,585µm) (p<0.01), except the DTC 32xCIM group (Sa 0,087µm, Sz 0,627µm). The porosity of the experimental groups was statistically higher than the control group (p<0,01). Conclusion: The incorporation of cerium nitrate resulted in reduction of flexural strength, in an increase of porosity, and the increase of surface roughness of the acrylic resin tested in all groups, except the DTC 32xCIM, despite this, the surface roughness values where is in the acceptable limit established in the literature.